The FDI and Many Economical Sectors Impact (Oil, Non-Oil) on Bahrain GDP: (An Econometrics Study for Period 1990-2021) - Jafaar, Mhamed Radhi; shani, Salam kazem; ALwaeli, Khudhair abbas Hassein (Journal of Ecohumanism, 2024)
Host countries work to attract foreign direct investment by creating an appropriate investment environment that meets the specifications required by multinational companies across continents, through which they seek to compensate for the deficit in local savings, as well as achieving a tangible increase in annual growth rates of the gross domestic product, as When multinational companies with experience and technology operate in host countries, they must train the local workforce in order to contribute to raising economic growth rates. The Kingdom of Bahrain has attracted foreign direct investment as a complement to local investment by transferring expertise and modern technology necessary to train and develop local cadres technically and technologically., Consequently, job opportunities increase, unemployment rates decrease, and production increases for the Kingdom of Bahrain, as Bahrain has entered the competition to attract foreign direct investment worldwide. Not only that, most of the investment is directed to important economic sectors such as the manufacturing and extractive industries sectors, and even part of the foreign trade sector, and therefore Their study of their impact on the gross domestic product and the analysis of economic relations shows the strength of both the effects of investment and economic sectors side by side in developing the Bahraini economy to keep pace with global changes in the field of energy and economic competition, despite the high progress in the field of investment at the international level that preceded it in this context., Since the investment coming into the Kingdom of Bahrain during the study period is low when compared with countries in the world that attract foreign direct investment, the research aims to measure the direct impact of foreign direct investment and some economic sectors on the gross domestic product using the Eviwes 12 program, and important results were obtained from the estimation.